Structure of coincidence isometry groups - Deng, Guixin; Zhao, Jinxing (Open mathematics (Warsaw, Poland), 2021)
Let be a lattice of rank in an -dimensional Euclidean space. We show that the coincidence isometry group of is generated by coincidence reflections if and only if contains an orthogonal subset of order